Deep brain stimulation with short versus conventional pulse width in Parkinson's disease and essential tremor: A systematic review and meta-analysis - Sara Smeets; Alexandra Boogers; Tine Van Bogaert; Jana Peeters; Myles McLaughlin; Bart Nuttin; Tom Theys; Wim Vandenberghe; Philippe De Vloo (Brain Stimulation, 2024)
Background: To maximize clinical benefit and minimize stimulation-induced side effects, optimising deep brain stimulation (DBS) parameters is paramount. Recent literature suggests a potential benefit of short pulse width DBS (spDBS; ≤40 μs) over conventional pulse width DBS (cDBS; ≥60 μs) in movement disorders. Objective: To compare therapeutic window (TW), therapeutic and side effects and energy consumption of spDBS and cDBS in movement disorders. Methods: We systematically searched Medline, Embase, Cochrane Library and Web of Science. Appropriate paired analyses were performed. Results: Nine Parkinson's disease (PD) (143 patients), 4 essential tremor (ET) (26 patients) and no dystonia studies were included in the meta-analysis. TW defined as therapeutic amplitude range was larger with spDBS vs. cDBS in PD (standardized mean difference (SMD) = -1.04, p < 0.001) and ET (SMD = −0.71, p < 0.001), but the TW in terms of charge per pulse (CPP) did not differ. In PD, no differences were found in therapeutic and side effects (MDS-UPDRS-III, speech and gait, dyskinesia, non-motor symptoms and quality of life). In ET, Fahn-Tolosa-Marin Tremor Rating Scale was lower with spDBS vs. cDBS (SMD = 0.36, p < 0.001). A qualitative analysis suggested fewer stimulation-induced side effects with spDBS. CPP was lower with spDBS vs. cDBS in PD (SMD = 0.79, p < 0.001) and ET (MD = 46.46 nC, p < 0.001), but real-world data on battery longevity are lacking. Conclusion: Although spDBS enlarges the TW as a wider amplitude range in both PD and ET, it does not alter TW defined by CPP. The therapeutic efficacy of spDBS is not different from cDBS in PD, but spDBS apparently induces more tremor reduction in ET.